Исследование и оптимизация рабочих характеристик ветроротора с вертикальной осью вращения с механизмом управления лопастями - Гринченко, В.Т.; Каян, В.П.; Кочин, В.А. (Видавничий дім "Академперіодика" НАН України, 2008)
The performance characteristics of vertical-axis wind rotors with the control mechanism of blades are studied. The results of experimental researches in a hydrotray and a wind tunnel are given. The self-start of such wind rotors at low speeds of the incident flow, a significant increase in both the operating ratio of a flow energy and the torque moment, and a decrease of the wind loads on the shaft relative to Darrieu-type wind rotors with rigidly fixed blades are demonstrated.